2009
DOI: 10.1007/bf03354620
|View full text |Cite
|
Sign up to set email alerts
|

Managing anxiety in eating disorders with knitting

Abstract: This preliminary data suggests that knitting may benefit inpatients with eating disorders by reducing their anxious preoccupations about eating, weight and shape control. The specificity of this effect is yet to be determined. This preliminary outcome requires further controlled study in AN subjects. From a clinical perspective, knitting is inexpensive, easily learned, can continue during social interaction, and can provide a sense of accomplishment. The theoretical and empirical rationale for this observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…From a clinical standpoint, knitting is gaining popularity with the young [11] as part of the wider resurgence of interest in craft activities and has been reported to have significant therapeutic benefits in both healthy and patient populations [12] , [13] , [14] . As such it is likely that more people who come to surgery may have interests and skills in knitting or similar craft activities as a pastime or hobby.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, knitting is gaining popularity with the young [11] as part of the wider resurgence of interest in craft activities and has been reported to have significant therapeutic benefits in both healthy and patient populations [12] , [13] , [14] . As such it is likely that more people who come to surgery may have interests and skills in knitting or similar craft activities as a pastime or hobby.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of positive health effects associated with creative arts have been similar to meditation and yoga (e.g., lower heart rate and blood pressure, decreased levels of the stress hormone cortisol, etc.). Knitting has helped women with eating disorders better manage their associated anxiety (Clave‐Brule, Mazloum, Park, Harbottle, & Birmingham, ). Increased feelings of happiness are associated with knitting among respondents experiencing chronic pain (Corkhill & Davidson, ).…”
Section: Community Program Incentive Definitionmentioning
confidence: 99%
“…Clave-Brule, Mazloum, Park, Harbottle, and Birmingham (2009) undertook a clinical study of adult women with eating disorders. Their findings reported that those engaged in knitting experienced a decrease in anxiety levels and preoccupation with their eating disorder (Clave-Brule et al, 2009). In her recent book, Textile Arts and Handcrafts in Art Therapy with Women: Weaving Lives Back Together, Collier (2011) explored the use of fiber crafts with participants in her private practice.…”
Section: Introductionmentioning
confidence: 98%